Efektivitas Program Dana Desa Pada Kondisi Covid-19 Di Desa Ngabar Kecamatan Siman Kabupaten Ponorogo - Anita Khoiriyah; Muhammad Mudjib Musta’in; Humaidah Muafiqie (Journal of Public Power, 2021)
Covid 19 has had many impacts on the village fund program, the effectiveness of the village fund program during the covid-19 pandemic, which aims to support the community's economy. With a descriptive qualitative approach model and carried out in Ngabar Village, Siman District, Ponorogo Regency, East Java with the object of research being the Ngabar village government, Siman District, Ponorogo Regency as the implementer of the village fund program. during the covid-19 pandemic in Ngabar village, Siman sub-district, Ponorogo district in 2020 it ran very effectively with a positive impact on efforts to empower the community